Micro-paper: volition in Speaking Participation (2023)
Speaking Participation Volition (SPV) refers to the intention or willpower of students in participating in oral communication activities. It includes creating a classroom environment that encourages and facilitates meaningful speaking opportunities for students to practice and improve their English speaking skills.